Moral Education Methods for Mentally Disabled Children at SLB Rela Bhakti I Gamping, Sleman, Yogyakarta - Maimanah, Ismah Fatatul; Darmadji , Ahmad (Universitas Islam Indonesia, 2023)
This study examines the implementation and effectiveness of various methods for moral education among intellectually disabled students at SLB Rela Bhakti I Gamping Sleman, a special education school in Yogyakarta, Indonesia. The study aims to evaluate specific teaching methods and their impact on students' moral and social development. A qualitative research design was employed, using observations, semi-structured interviews with teachers, and document analysis to gather data. Nine teaching methods were identified and analyzed: lectures, role modeling, habituation, demonstrations, direct practice, thematic learning, group discussions, field trips, and peer learning. These methods were examined for their adaptability and effectiveness in addressing the unique challenges faced by intellectually disabled students. The findings reveal significant improvements in students' social behaviors, empathy, and moral decision-making. Methods such as role modeling and habituation were particularly effective in reinforcing positive behaviors, while thematic learning and field trips provided practical applications of moral concepts. Despite these successes, challenges such as resource limitations, diverse student needs, and inconsistent parental involvement were identified as barriers to implementation. This study contributes to the growing field of inclusive education by offering actionable insights into the integration of moral education for intellectually disabled students. The findings underscore the importance of collaborative efforts among educators, families, and policymakers to create supportive learning environments. Future research should explore long-term impacts and the potential of emerging technologies to enhance engagement and accessibility in moral education.